3D printed interdigitated supercapacitor using reduced graphene oxide-MnOx/Mn3O4 based electrodes. Issue 27 (13th June 2022) - Mokhtarnejad, Mahshid; Ribeiro, Erick L.; Mukherjee, Dibyendu; Khomami, Bamin
Abstract : LASiS-based HNCs of nanostructured MnO x /Mn3 O4 . Abstract : In this study hybrid nanocomposites (HNCs) based on manganese oxides (MnO x /Mn3 O4 ) and reduced graphene oxide (rGO) are synthesized as active electrodes for energy storage devices. Comprehensive structural characterizations demonstrate that the active material is composed of MnO x /Mn3 O4 nanorods and nanoparticles embedded in rGO nanosheets. The development of such novel structures is facilitated by the extreme synthesis conditions (high temperatures and pressures) of the liquid-confined plasma plume present in the Laser Ablation Synthesis in Solution (LASiS) technique. Specifically, functional characterizations demonstrate that the performance of the active layer is highly correlated with the MnO x /Mn3 O4 to rGO ratio and the morphology of MnO x /Mn3 O4 nanostructures in HNCs. To that end, active layer inks comprising HNC samples prepared under optimal laser ablation time windows, when interfaced with a percolated conductive network of electronic grade graphene and carbon nanofibers (CNFs) mixture, indicate superior supercapacitance for functional electrodes fabricated via sequential inkjet printing of the substrate, current collector layer, active material layer, and gel polymer electrolyte layer. Electrochemical characterizations unequivocally reveal that the electrode with the LASiS synthesized MnO x /Mn3 O4 –rGO composite exhibits significantly higher specific capacitance compared to the ones produced with commercially available Mn3 O4 –graphene NCs. Moreover, the galvanostatic charge–discharge (GCD) experiments with the LASiS synthesized HNCs show a significantly larger charge storage capacity (325 F g −1 ) in comparison to NCs synthesized with commercially available Mn3 O4 –graphene (189 F g −1 ). Overall, this study has paved the way for use of LASiS-based synthesized functional material in combination with additive manufacturing techniques for all-printed electronics with superior performance.